Lymph nodes dissection in advanced ovarian cancer - V. S. Svintsitskiy; N. P. Tsip; S. V. Nespryadko; V. I. Kopetskyi; M. Y. Yegorov; O. M. Movchan; O. P. Renkas; O. I. Bubliieva (Publishing House TRILIST, 2020)
Ovarian cancer becomes the most aggressive disease among all cancer pathology in women's reproductive system. Surgery and chemotherapy are the main options on the way of ovarian cancer treatment. Cytoreductive surgeries are the main way of surgical treatment of patients with advanced ovarian cancer. The goal of this kind of surgeries is resections of all macroscopic implants. The opportunity of systematic lymph nodes dissection from renal vessels to obturator nerve is the reason of scientific discussion. LION trial (Lymphadenectomy In Ovarian Neoplasms) showed no significant difference in overall survival in two groups of patients with advanced ovarian cancer with IIВ-IV stages, who performed systematic lymphadenectomy and who did not. Authors showed higher level of postoperative complications in group with systematic lymph node dissections. But it was analyzed only those patients, who had intraoperative clinically insignificant lymph nodes. However, if the lymph nodes are macroscopically changed, performing a lymphadenectomy is advisable in order to achieve complete cytoreduction. Purpose of the study: assessment of lymph nodes dissection in patients with advanced ovarian cancer. Materials and methods. Retrospective analysis of patients with primary ovarian cancer IIIC-IV stages with clinically significant lymph nodes, which were subjected to interval or primary cytoreduction with systematic lymphodissection from the level of renal vessels to the obturator pit. Results. Complete and optimal cytoreduction was achieved in patients with systemic para-aortic and pelvic lymphodissection from the level of renal vessels to the obturator pit, which was not accompanied by postoperative complications and fatality. Conclusion. The study results demonstrates the possibility of safe systemic lymphodissection, which contributes to the achievement of complete or optimal cytoreduction, and improves the rates of disease-free survival.